1987
DOI: 10.1051/forest:19870402
|View full text |Cite
|
Sign up to set email alerts
|

Le dépérissement du sapin dans les Vosges : rôle primordial de déficits d'alimentation en eau

Abstract: RésuméPour étudier ce dépérissement, une méthode facilitant l'interprétation des différences d'état de santé entre peuplements a été retenue. Huit

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
1
5

Year Published

1990
1990
2006
2006

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 0 publications
0
9
1
5
Order By: Relevance
“…Senones and Voltzia sandstones which are located at low altitude (generally less than 500 m) provide a higher percentage of clay than the Vosgian sandstone, which is located at higher altitude (generally more than 550 m). Other studies carried out in the Vosges and the Jura [5] [7,17] found a significant relationship between silver fir decline and the plant available water holding capacity of the soil.…”
Section: Climatic Factorsmentioning
confidence: 99%
“…Senones and Voltzia sandstones which are located at low altitude (generally less than 500 m) provide a higher percentage of clay than the Vosgian sandstone, which is located at higher altitude (generally more than 550 m). Other studies carried out in the Vosges and the Jura [5] [7,17] found a significant relationship between silver fir decline and the plant available water holding capacity of the soil.…”
Section: Climatic Factorsmentioning
confidence: 99%
“…Den-dochronological and biogeochemical investigations in the Vosges massif (eastern France) suggested that the decline of spruce in eastern France and western Germany might be mainly related to repeated severe drought events that had occurred since the mid-1970s in these regions (Lévy and Becker, 1987;Probst et al, 1990). Further research on spruce decline therefore requires more knowledge of the ecophysiological behaviour of mountain spruce under long-term soil drought.…”
Section: Introductionmentioning
confidence: 99%
“…Our understanding of its ecological amplitude is essentially based on the study of its natural range; this conifer cannot tolerate late frosts and dry summers and is the major component of mountain forests (900 to 1 500 m of elevation) where atmospheric humidity is high. Dendrochronological and dendro-ecological studies emphasize the high sensitivity of silver fir to water stress (Bîndiu, 1971;Serre-Bachet, 1986;Levy and Becker, 1987;Becker, 1989) while experiments on young potted trees show that it conserves water quite well (Becker, 1970(Becker, , 1977 and in particular better than Norway spruce (Picea excelsa Link) with which it is frequently mixed in mountain stands. However, silver fir appears to delay the regulation of its water-vapor exchanges, which classifies it among species that are poorly adapted to drought (Aussenac, 1980).…”
Section: Introductionmentioning
confidence: 99%